The effectiveness of using digital animated videos in teaching underhand passing in volleyball at SMK 1 Jenangan, Ponorogo Regency - Bayu Purwo Adhi; Arief Abdul Malik; Indra Sholehudin; Agus Martins (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2026)
Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan video animasi digital dalam meningkatkan keterampilan teknik passing bawah bola voli siswa SMK 1 Jenengan Kabupaten Ponorogo. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan desain siklus yang terdiri dari tiga tahap, yaitu pra-siklus, siklus I, dan siklus II. Setiap siklus melibatkan penggunaan video animasi digital sebagai media pembelajaran untuk memperagakan gerakan teknik passing bawah secara lebih jelas dan terstruktur. Data dikumpulkan melalui observasi terhadap keterampilan teknik passing bawah siswa yang diukur dengan menggunakan Kriteria Ketuntasan Minimal (KKM). Hasil penelitian menunjukkan adanya peningkatan signifikan dalam hasil belajar siswa dari pra-siklus ke siklus II. Pada pra-siklus, hanya 40% siswa yang mencapai KKM, sedangkan pada siklus II, jumlah siswa yang tuntas mencapai 85,71%. Peningkatan ini menunjukkan bahwa video animasi digital efektif dalam membantu siswa memahami dan mempraktikkan teknik dasar bola voli, terutama dalam meningkatkan keterampilan psikomotorik. Dengan demikian, penggunaan video animasi digital dapat menjadi alternatif media pembelajaran yang efektif dalam mengajarkan keterampilan olahraga di tingkat SMK. Abstract:This study aims to analyze the effectiveness of utilizing digital animation videos in improving the underhand passing skills of students at SMK 1 Jenengan, Ponorogo Regency. The research employs the Classroom Action Research (CAR) method, utilizing a cycle design consisting of three stages: pre-cycle, Cycle I, and Cycle II. Each cycle involves the use of digital animation videos as a learning medium to demonstrate the underhand passing technique in a more transparent and structured manner. Data were collected through observations of students' underhand passing skills, which were measured utilizing the Minimum Mastery Criteria (KKM). The results show a significant improvement in student learning outcomes from the pre-cycle to cycle II. In the pre-cycle, only 40% of students achieved the KKM, while in cycle II, the percentage of students who completed the KKM increased to 85.71%. This improvement indicates that digital animation videos are effective in helping students understand and practice basic volleyball techniques, particularly in enhancing psychomotor skills. Therefore, the use of digital animation videos can serve as an effective alternative learning medium for teaching sports skills at the vocational school level.